Analysis of The Students’ Engagement in The Process of Learning Mathematics Using a Flipped-classroom Approach to Trigonometry - Nugraheni, Maria Magdalena Yunika; Suryaningrum, Parmamita; Rudito, M. Andy (Universitas Sebelas Maret, 2022)
The COVID-19 pandemic that has hit various regions of the world has an impact on various sectors, including the education sector. This causes teaching and learning activities to be carried out online to minimize the transmission of this pandemic. However, online learning experiences several challenges for both teachers and students, one of which is students’ engagement where students tend to be passive and only accept the material provided by the teacher. This causes teachers to design creative and interesting learning to make students interested and active both emotionally, cognitively and student behavior. Flipped classroom is a learning approach where the teacher guides concepts effectively by creating an interactive learning environment that provides opportunities for students to participate actively. The aims of this research are 1) Knowing the learning design using flipped classroom to increase student involvement in learning mathematics. 2) Knowing the effect of flipped classroom in increasing student’s engagement in learning. The method used is a literature review and quantitative through a questionnaire. The subjects of this study were students of class X who took part in learning mathematics with a flipped classroom approach on trigonometry material. This study resulted in a learning design in the form of a learning design using a flipped classroom to increase student engagement. In addition, based on the results of the questionnaire, it can be concluded that the flipped classroom has an effect on increasing student’s engagement in learning mathematics.